Pengaruh Modal Sendiri Dan Hutang Terhadap Profitabilitas Perusahaan Textile Garmen Yang Go Public Di Bursa Efek Indonesia (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2020)
Maimunah. 2019, Effect of Equity and Debt To Profitability In the Company went public in Indonesia Stock Exchange. Under the guidance of Mrs. Yana Ulfah and Mr. Rusliansyah. This research was conducted at the Garment Textile company that went public in Indonesia Stock Exchange (BEI). The purpose of this study was to analyze the effect of Equity, Debt Short-Term and Long-Term Debt to Profitability in Garment Textile company that went public on the Stock Exchange from 2013 to 2017 period. This study using multiple linear regression method with SPSS version 23. These results indicate that the variable Equity positive effect was not significant, positive impact Short-Term Debt and Long-Term Debt significant positive effect significantly.